(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The word constipation refers to the bowel movements that are infrequent or hard to pass, causing discomfort the individual. The stools are often hard, dry and small making them painful or difficult to pass. Acharya Sushrutha has mentioned a special formulation called Madanadi Guda Varti in the context of Udararoga Chikithsa which has been lost with the passage of time and there are no references of its usage in modern times. The aim of this study is to evaluate the role of Madanadi Guda Varti in the management of constipation. Methodology: It is a case study of a 45 years old female patient who presented with the chief complaints of constipation with abdominal discomfort since 3 days. She was treated with the prepared Madanadi Guda Varti, a suppository, which was inserted per anus. Results: Complete evacuation of stools was achieved within 3 hours of insertion of the suppository. Discussion: Constipation is a common complaint and needs to be assessed irrespective of the specialties in medical practice. In this present case, Madanadi Guda Varti has shown promising results in the successful management of constipation with ease and is devoid of any complications. Further clinical studies are required to evaluate its effectiveness in larger sample.